2018
DOI: 10.1080/07481187.2018.1480546
|View full text |Cite
|
Sign up to set email alerts
|

Further validation of the Traumatic Grief Inventory-Self Report (TGI-SR): A measure of persistent complex bereavement disorder and prolonged grief disorder

Abstract: The Traumatic Grief Inventory Self-Report version (TGI-SR) is an 18-item self-report measure. It was designed to assess symptoms of Persistent Complex Bereavement Disorder (PCBD) included in Diagnostic and Statistical Manual of Mental Disorders (DSM)-5 and Prolonged Grief Disorder (PGD) proposed by an international group of experts in grief. The research in this article used data from a bereaved patient sample and people who lost loved ones in the Ukrainian airplane crash in July 2014. Findings indicated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
5
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 92 publications
(59 citation statements)
references
References 27 publications
(51 reference statements)
3
46
5
5
Order By: Relevance
“…The TGI sum score provides an index of severity of the grief symptoms, with a higher score associated with higher grief severity (range, 18 to 90). The TGI-SR has been validated in both a patient and a community sample (28). The internal consistency in the current study was good (Cronbach's alpha at T1 =.84 and at T2 =.92).…”
Section: Measurements and Data Collectionmentioning
confidence: 61%
“…The TGI sum score provides an index of severity of the grief symptoms, with a higher score associated with higher grief severity (range, 18 to 90). The TGI-SR has been validated in both a patient and a community sample (28). The internal consistency in the current study was good (Cronbach's alpha at T1 =.84 and at T2 =.92).…”
Section: Measurements and Data Collectionmentioning
confidence: 61%
“…The DSM-5 lists a partly different concept, persistent complex bereavement disorder (PCBD), as a condition requiring further research (American Psychiatric Association, 2013). The two PGD concepts, Prigerson et al's (2009) PGD and DSM-5 PCBD, largely overlap with regard to symptoms, prevalence rates, and correlates, suggesting that they identify similar diagnostic entities (Boelen, Djelantik, de Keijser, Lenferink, & Smid, 2018;Maciejewski, Maercker, Boelen, & Prigerson, 2016). PGD can be discriminated from related disorders such as PTSD and depression (e.g.…”
Section: 德国避难者的延长哀伤障碍:丧亲和居留状态的影响mentioning
confidence: 99%
“…However, the advancement of our knowledge of this disorder requires standardized assessment tools that correspond to these criteria. As mentioned above, existing scales have sound psychometric properties and an ability to capture grief reactions with functional impairment (Prigerson et al, 1995;Lichtenthal et al, 2011;Carmassi et al, 2014;Papa et al, 2014;Boelen and Smid, 2017;Boelen et al, 2018a;Pohlkamp et al, 2018), but these scales do not precisely capture ICD-11 PGD and lack evaluation of diagnostic test accuracy. There is a need for both valid structured clinical interviews for ICD-11 PGD and valid self-report scales for ICD-11 PGD with adequate diagnostic test accuracy and a valid clinical cut off.…”
Section: Discussionmentioning
confidence: 99%
“…The ICG and its successors, particularly ICG-R and PG-13, are the instruments used in most frequently by studies supporting both ICD-11 PGD and PCBD criteria, and are the scales that most closely resembles ICD-11 PGD. Although studies have found these measures of prolonged grief to have sound psychometric properties, including internal consistency, test-retest reliability, and construct, concurrent, convergent and criterion validity (Prigerson et al, 1995;Lichtenthal et al, 2011;Carmassi et al, 2014;Papa et al, 2014;Boelen and Smid, 2017;Boelen et al, 2018a;Pohlkamp et al, 2018), none correspond directly to the ICD-11 PGD definition.…”
Section: The State Of Current Instruments Measuring Prolonged Grief Dmentioning
confidence: 99%